MEDIA EDUKASI VIDEO LEBIH EFEKTIF DIBANDINGKAN MEDIA BOOKLET SEBAGAI PROMOSI KESEHATAN PENCEGAHAN OBESITAS PADA REMAJA - Rosanti, Dwike; Muhamad Fadlullohil Hakim Nurdiyanto; Valda Gilby Renata, Tri; Ningrum, Selfya (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of health promotion through the media must reflect the latest advances. One of the interesting innovations in health promotion is the use of visual video media in health promotion to improve health. The aim of this research is to show that the use of video media is more effective than brochures in increasing knowledge, attitudes and practices regarding nutrition and obesity prevention in a group of adolescents. The research method used was a two-group experimental design with a total of 750 high school students. Data collected includes nutritional knowledge, nutritional attitudes and eating habits.The data analysis technique uses an independent sample t-test. Data analysis shows that health promotion using video media is superior to pamphlet media because it significantly increases nutritional knowledge, attitudes and practices (p<0,000). The research findings revealed that the participants who received video intervention demonstrated greater improvement in their understanding, attitudes, and behaviors towards nutrition when compared to those who relied on booklets.